The evolving roles of geophysics in environmental assessment, monitoring, and management of landfill leachate contaminant plumes: An overview - Joseph Omeiza Alao (Case Studies in Chemical and Environmental Engineering)
Landfill leachate, a toxic brew of pollutants, poses a silent threat to water resources, ecosystems, and public health. Traditional monitoring methods struggle to grasp the full extent of this danger, leaving us blind to the insidious spread of contamination. This review highlights the crucial involvement of geophysics as a powerful tool to peer beneath the surface and unravel the mysteries of LLPs to address these challenges, showcasing its ability to detect, map, characterize, and monitor LLPs with unprecedented detail. The study examined the effectiveness of geophysical methods such as resistivity, seismic, electromagnetic (EM), and magnetic, heightening their strengths and limitations. Electrical resistivity Imaging (ERI) and ground penetrating radar (GPR) show higher strength in assessing and monitoring LLP contaminant plumes, seismic refraction tomography (SRT) and ground magnetic survey (GMS) show moderate strength with very low-frequency EM (VLF-EM) technology falls short, especially in detecting and mapping disjoint subsurface contaminant plumes. Comparative studies from different geophysical methods from noteworthy literature show that LLPs often exhibit geophysical properties (density, magnetism, or conductivity) higher or lower than the host environment, allowing geophysical tools to detect and map them at rapid speed, low cost, and high accuracy and resolution, without surface/subsurface invasion and secondary contamination intrusion. Despite the significant contribution of geophysical techniques in understanding the behaviour of LLPs within the subsurface, it may not replace direct investigations such as geological borehole data and geochemical water analysis completely for adequate environmental monitoring. However, some key influencing factors such as subsurface porosity, hydraulic conductivity, redox conditions, heterogeneity contaminant, geological properties, water soil contents, and groundwater flow dynamics, seem to have a significant influence on the geophysical data acquisition, potentially projecting false positive/negative results. Case studies demonstrated where geophysics stands and delivers in enhancing the understanding of LLPs, guiding sustainable waste management practices. In conclusion, geophysics offers a non-invasive, cost-effective, and high-resolution approach to LLP management. Future research should focus on developing advanced data interpretation techniques, integrating geophysical data with other environmental monitoring data, and exploring the use of artificial intelligence for automated analysis and prediction of LLP behaviour, which ultimately aiding the environmental decision-makers in addressing ecological challenges and designing/managing landfill sites.